Toxicity for Control of Frankliniella schultzei and Selenothrips rubrocinctus (Thysanoptera: Thripidae) of Several Common Synthetic Insecticides - Manlika Kilaso (Florida Entomologist, 2022)
Thrips are serious pests of several kinds of crop plants throughout the world. Their attack leads to loss in plant production. Common blossom thrips, Frankliniella schultzei (Trybom), and red-banded thrips, Selenothrips rubrocinctus (Giard) (both Thysanoptera: Thripidae), are serious insect pests attacking various plants, such as tomato (Solanum esculentum Miller [Solanaceae]), mango (Mangifera indica Linnaeus [Anacardiaceae]), avocado (Persea americana Miller [Lauraceae]), and lotus flower (Nelumbo nucifera Gaertn. [Nelumbonaceae]). Currently, basic thrips control relies on synthetic insecticides. However, the toxicity of each existing insecticide for control of some specific pest species still has not been well established. This study evaluated and reported the toxicity of 6 insecticides (chlorantraniliprole, cypermethrin, carbosulfan, fipronil, abamectin, and spinetoram) for control of the 2 thrips species mentioned above. The evaluation was done by exposing 10 thrips to a bean dipped in insecticide, and mortality was recorded after 24 h of exposure under laboratory conditions. Spinetoram was the most toxic to F. schultzei with an estimated LC 50 of 0.05 ng per L. For red-banded thrips, S. rubrocinctus, the most toxic insecticides were abamectin, spinetoram, and fipronil, with LC 50 values of 1.67, 1.85, and 4.23 ng per L, respectively. On the other hand, the least toxic insecticide to common blossom thrips and red-banded thrips was chlorantraniliprole, with LC 50 values of 270.51 and 641.08 ng per L, respectively. Overall, among the tested chemicals, spinetoram was the most effective in controlling these pests. The findings from this study will benefit developers of insecticide management strategies in thrips control programs.
Keywords: Insect-Plant Interactions and Control; Insect Pest Control Strategies; Insect and Pesticide Research